The Impact of Audit Quality Indicators on the Timeliness of Goodwill Impairments: Evidence from the German Setting. (25th February 2020) - Albersmann, Benjamin T.; Quick, Reiner
Abstract : This study investigates whether goodwill impairments are perceived as timely and whether specific auditor characteristics affect the perceived timeliness. It therefore contributes to central questions in accounting research: is managerial discretion over accounting numbers (accounting choice) good or bad for stakeholders and does audit quality have an impact on this relationship? It is motivated by the IASB's post‐implementation review on business combinations and the Goodwill and Impairment project based on it, the ongoing debate on the decision usefulness of impairment testing, and the question whether auditors have an impact on firms' reporting of impairment losses. Based on a sample of German listed firms for the period 2006 to 2013, the results indicate that goodwill impairments are not recognized in a timely manner and delayed by at least one to two years. Moreover, the findings suggest that the recognition of impairment losses is influenced by auditor characteristics. In particular, firms seem to report goodwill impairments in a more timely fashion when they are audited by a Big 4 auditor, whereas the timeliness seems to decrease with a higher non‐audit fee ratio and a longer auditor tenure. Moreover, additional analyses indicate that higher audit fees lead to more timely impairments.